2004
DOI: 10.1111/j.1553-2712.2004.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Educational Web Site for Educating Physicians about Bioterrorism

Abstract: Objectives: To determine whether a Web-based educational intervention improves emergency physicians' knowledge about bioterrorism and to survey physicians' knowledge and sources of information on bioterrorism. Methods: Prospective randomized controlled trial using pre-and postintervention testing in hospitals. Participants were general and pediatric emergency medicine attending physicians, fellows, and fourth-year emergency medicine residents. All participants completed a pretest and attended a lecture on biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…One attractive method of disseminating information in terms of cost and accessibility are web-based programs. Those utilizing a passive learning process have reported mixed success (Chung et al 2004;Terndrup et al 2005). An interactive, case-based online module significantly improved Internal Medicine resident and attending physician's short term level of knowledge regarding potential biologic agents (Cosgrove et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One attractive method of disseminating information in terms of cost and accessibility are web-based programs. Those utilizing a passive learning process have reported mixed success (Chung et al 2004;Terndrup et al 2005). An interactive, case-based online module significantly improved Internal Medicine resident and attending physician's short term level of knowledge regarding potential biologic agents (Cosgrove et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are likely to be among the first responders to an occult bioweapon attack. Since early recognition of specific disease entities and appropriate reporting to public health authorities may decrease overall morbidity and mortality and improve our ability to contain the spread of transmissible disease, physician education is a vital part of our defense (Artenstein et al 2002;Chung et al 2004;Wynia & Gostin 2004;Cosgrove et al 2005). Unlike basic life support (BLS) and advanced cardiac life Support (ACLS) training, biodefense is not well integrated into the curricula of most internal medicine residency or pulmonary and critical care medicine fellowship programs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 A recent survey of emergency physicians supported the development and implementation of comprehensive bioterrorism preparedness plans to resolve deficiencies, including physician education and training. 1 A prospective, randomized trial of an educational Web site for educating physicians about bioterrorism demonstrated no increase in knowledge, 3 but 30% of physicians randomized to the site did not access it despite weekly e-mail prompts. Of those who did access the site (total, 17), one third spent 20 minutes or less on the site.…”
mentioning
confidence: 99%